Linga Longa - Stories of Women and Thirroul. - Christian, Kerrie Anne ([Australia]: Kerrie Anne Christian, 2009)
"LingaLonga is an old house in Thirroul, the village where my family have lived for generations. I wanted to know more about the stories of interesting women who lingered in Thirroul - mostly they passed through quietly, as the village nurtured & inspired them. This page is a workspace, exploring their lives, as they lived, worked, died or visited in Thirroul. Alas professional demands drew me away from writing for nearly 3 years. However now I have returned to share more stories. Kerrie Anne Christian"
Title from title screen (viewed on 20 October 2020)
Mode of access: Available Online. Address as at 30/10/2020
Selected for archiving
Keywords: Genealogy; Australian